Sistem Konten Pembelajaran di Indonesia : Systematic Literature Review - Dhomas Hatta Fudholi; Insanur Hanifuddin; Sri Mulyati (Faculty of Engineering and Informatics, Universitas Multimedia Nusantara, 2021)
Wikipedia is the largest web-based digital encyclopedia today that contains almost all knowledge in general. On Wikipedia many readers have difficulty finding accurate information about the topic they are looking for, as content on Wikipedia usually contains only an overview of the topic referenced from some existing references. This study aims to examine Wikipedia, other encyclopedias and other online media that contain specific topics with their target users. The study was conducted on literature related to Wikipedia, encyclopedias, education and children's interests, especially at the elementary school level. Literature search is done by including some of the main keywords in Google Scholar such as